Análise envoltória de dados para avaliação da eficiência da tilapicultura brasileira - Sabbag, Omar Jorge [UNESP] (My University, 2019)
Tilapicultura presents an important segment of social and economic development, considering the potential of natural resources in Brazil. The main contribution of this thesis is related to the management process in the main tilapia producing regions of the country, which is not just a question of generating economic indicators. Within this theme, as a proposal to measure an efficiency evaluation, through Data Envelopment Analysis (DEA analysis), the objective of this study was to evaluate the performance of the main poles producing tilapia in Brazil, in order to generate information that effectively contributes to actions aimed at efficiency gains and competitiveness in the productive sector, as well as to find the determinants of inefficiency through the Tobit econometric model. It observed that between the poles there was a variation between 41 and 85% of global efficiency, due to the characteristics of each region, as well as the management of the factors of production. Among the variables that had a positive influence on efficiency were the collective organization, technical assistance and technology adopted; in the same way, absence of technology, assistance, as well as indebtedness were pointed as negative variables to productive performance. It concluded that in the near future, the good manager would be represented by the greater productive efficiency, generating a reduction of its costs and improving its profits in market mishaps in which the producer is a price-taking agent, considering a competitive and growing scenario for national tilapia farming.

A tilapicultura apresenta um importante segmento de desenvolvimento social e econômico, considerando a potencialidade de recursos naturais no Brasil. A principal contribuição da presente tese está relacionada ao processo de gestão nas principais regiões produtoras de tilápia do país, que não se resume apenas gerar indicadores econômicos. Dentro desta temática, como proposta de mensurar uma avaliação de eficiência, por meio da Análise Envoltória de Dados (análise DEA), objetivou-se avaliar o desempenho dos principais polos produtores de tilápia no Brasil, de forma a gerar informações que contribuam efetivamente para ações que visem ganhos de eficiência e competitividade no setor produtivo, bem como encontrar os fatores determinantes da ineficiência, por meio do modelo econométrico Tobit. Observou-se que entre os polos houve uma variação entre 41 e 85% de eficiência global, em razão das características de cada região, bem como a gestão dos fatores de produção. Dentre as variáveis que influenciaram positivamente na eficiência, destacaram-se a organização coletiva, assistência técnica e tecnologia adotada; da mesma forma, ausência de tecnologia, assistência, bem como endividamento foram apontados como variáveis negativas ao desempenho produtivo. Concluise que em um futuro próximo, o bom gestor será representado pela maior eficiência produtiva, gerando uma redução de seus custos e melhorando seus lucros em contratempos de mercado no qual o produtor é um agente tomador de preços, considerando um cenário competitivo e crescente para a tilapicultura nacional. Tilapicultura presents an important segment of social and economic development, considering the potential of natural resources in Brazil. The main contribution of this thesis is related to the management process in the main tilapia producing regions of the country, which is not just a question of generating economic indicators. Within this theme, as a proposal to measure an efficiency evaluation, through Data Envelopment Analysis (DEA analysis), the objective of this study was to evaluate the performance of the main poles producing tilapia in Brazil, in order to generate information that effectively contributes to actions aimed at efficiency gains and competitiveness in the productive sector, as well as to find the determinants of inefficiency through the Tobit econometric model. It observed that between the poles there was a variation between 41 and 85% of global efficiency, due to the characteristics of each region, as well as the management of the factors of production. Among the variables that had a positive influence on efficiency were the collective organization, technical assistance and technology adopted; in the same way, absence of technology, assistance, as well as indebtedness were pointed as negative variables to productive performance. It concluded that in the near future, the good manager would be represented by the greater productive efficiency, generating a reduction of its costs and improving its profits in market mishaps in which the producer is a price-taking agent, considering a competitive and growing scenario for national tilapia farming.
Data envelopment analysis to evaluate the efficiency of brazilian tilapiculture
Keywords: DEA analysis; Performance; Management; Tobit model; Análise DEA; Desempenho; Gestão; Modelo Tobit; Tilápia